Behind the Façade: Collapse of the Rural Community Myth in "Broadchurch" - Kiersnowska, Beata (Zagadnienia Rodzajów Literackich, 2025)
The article discusses the process of disintegration of a small-town community in the fictional town of Broadchurch, depicted in the first series of a British crime drama under the same title. Although the complete Broadchurch series comprises of three seasons, only the first one was chosen for the present analysis due to its relevance to the topic under discussion. In the eight episodes of the first season, its creator, Chris Chibnall, unravels not only the mystery of a local boy’s murder but also the way this crime and the ensuing police investigation affect the local community. The present analysis is situated within a broader historical and cultural context of the dichotomous perception of the country and the city, which has entrenched a highly positive and idealised image of small rural communities in British society and culture. The scholarly literature on community-forging factors and processes from the realm of social studies has provided the author with basic concepts and instruments to examine the gradual breakdown of community cohesion in Broadchurch, triggered by murder-induced collective trauma. The paper has also been informed by works from the field of film studies offering a broad perspective on the varied representations of rural communities in British cinematic and television productions. The article presents Chris Chibnall’s Broadchurch as a work that deconstructs the romanticised perception of close-knit ‘Gemeinschaft’ communities celebrated in British literary and popular culture works.